Hubungan Antara Hipertensi dan Usia dengan Angka Kejadian Kanker Payudara Di RSUD Dr. H. Abdul Moeloek Bandar Lampung Tahun 2018 - Muhartono; Rizki Hanriko; Waluyo Rudiyanto; Mohamad Reihansyah Deswindra (CV. Jasa Sukses Abadi, 2020)
Breast cancer is one of the most highest incidence rate cancer in all countries. Age and Hypertension is known as risk factor for breast cancer. The purpose of this study is to know the relation between hypertension and age with breast cancer incidence rates in Dr. H. Abdul Moeloek Bandar Lampung. The method of this study is observational analytic study with case control design. The data that used are secondary data that gathered from medical records of patients in Dr. H. Abdul Moeloek Hospital and taken with consecutive sampling method. The data is analyzed using univariate and bivariate analysis using Chi-square test and Fisher test. The result is in the case group, hypertension percentage obtained was 12.5% ​​while those whose has not hypertension was 87.5%. In the control group the percentage of hypertension was 8.3% while those whose has not hypertension was 91.7%. In the case group ≥50 years of age percentage obtained was 54.2% while at age <50 years was 45.8%. In the control group ≥50 years of age percentage of 16.7% while at age <50 years at 83.3%. The results showed that age ≥50 years have a p value = 0,007 with OR = 5,909 and hypertension group have a p value = 0.500. The conclusion of this study is, there is no the relationship between hypertension and breast cancer incidence rates Lampung and there is relationship between the age of patients with breast cancer incidence rates in the Hospital of Dr. H. Abdul Moeloek Bandar Lampung.